Hidden negative energies in strongly accelerated universes - Sawicki, Ignacy; Vikman, Alexander (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We point out that theories of cosmological acceleration which have equation of state, w, such that 1+w is small but positive may still secretly violate the null energy condition. This violation implies the existence of observers for whom the background has infinitely negative energy densities, despite the fact that the perturbations are free of ghosts and gradient instabilities.
Gesehen am 01.02.2022